2017
DOI: 10.1016/j.heliyon.2017.e00352
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization of human immunodeficiency virus type 1 transmission in the Middle East and North Africa

Abstract: BackgroundThe HIV-1 spread in the Middle East and North Africa (MENA) has not been previously characterised using the phylogenetic approach. The aim of the current study was to investigate the genetic diversity and domestic transmission of HIV-1 in the MENA.MethodsA total of 2036 HIV-1 sequences available in Genbank and collected in the MENA during 1988–2016 were used together with 715 HIV-1 reference sequences that were retrieved from Genbank based on genetic similarity with the MENA sequences. The REGA and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
9
1
Order By: Relevance
“…Recent analyses suggest that COMET HIV-1 v2.2 has shown superior specificity in short sequences. 32,35 Despite the fact that subtype and intersubtypes had been reported in PR [B/F, B/D, A1/B, A(A2), A(01-AE), F(12-BF), and CRF39-BF] previously, this is the first report of subtypes C, D, and CRF-24BG (Fig. 3).…”
Section: Resultsmentioning
confidence: 66%
“…Recent analyses suggest that COMET HIV-1 v2.2 has shown superior specificity in short sequences. 32,35 Despite the fact that subtype and intersubtypes had been reported in PR [B/F, B/D, A1/B, A(A2), A(01-AE), F(12-BF), and CRF39-BF] previously, this is the first report of subtypes C, D, and CRF-24BG (Fig. 3).…”
Section: Resultsmentioning
confidence: 66%
“…Phylogenetic inference can be used to investigate the proportion of domestic spread of viruses and to test hypotheses related to variables that are associated with higher likelihood of transmission ( Lin et al, 2005 ; Pybus & Rambaut, 2009 ; Sallam et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiology of HIV transmission is known to be changed over time from one region to another and from one country to another within the same region . [15] In the present study, sexual behavior mainly through heterosexuals, represents the main route of HIV transmission. Previously, from 1986-2005, El-Ebadi et al, found that 84.5% of new HIV Iraqi cases were transmitted by parenteral route mainly through blood donation, while sexual practice is responsible for 11.3% of the cases.…”
Section: Discussionmentioning
confidence: 88%